Firm-specific characteristics and the timing of foreign direct investment projects - Horst Raff; Michael Ryan (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper uses a proportional hazard model to study foreign direct investment by Japanese manufacturers in Europe between 1970 and 1994. We divide each firm's investment total into a sequence of individual investment decisions and analyze how firm-specific characteristics affect each decision. We find that total factor productivity is a significant determinant of a firm's initial and subsequent investments. Parent-firm size does not have a significant influence on the initial decision to invest. Large firms simply have more investments than smaller firms. Other firm-specific characteristics, such as the R&D intensity, export share and keiretsu membership, also play a role in the investment process.
Keywords: F23; L20; 330; Direktinvestition; Japanisch; Multinationales Unternehmen; Produktivität; Keiretsu; Schätzung; Japan; Europa